Multidimensional Analysis of Voice in Parkinson's Disease Patients: A Case Study - Jara Cabrera, Gerson; Peralta Castillo, Carolina; Gallegos Lobos, Dafna; Sepúlveda Ordiqueo, Carlos; Carrasco Currín, Paula; Higuera Seguel, Cristianne; Gálvez Pino, Catalina (Revista de Investigación en Logopedia, 2025)
Parkinson's disease (PD) is a neurodegenerative disorder that affects the central nervous system, characterized by motor and non-motor clinical manifestations. Among the motor difficulties is hypokinetic dysarthria, which affects the voice of those with the disease. The purpose of this study is to describe, from a multidimensional perspective of voice, aspects such as acoustic, aerodynamic, and laryngoscopic measures in a group of subjects with PD. For this purpose, a descriptive cross-sectional study was conducted, evaluating 10 subjects with PD in different stages of the disease's progression. Acoustic parameters were evaluated using the Praat program, maximum phonation time, and glottic configuration through nasofibrolaryngoscopy. In the acoustic evaluation, a variation in fundamental frequency was found, being slightly increased in males and decreased in females. Jitter was within normal range. Four subjects showed an increased shimmer value, and two had increased noise levels. The alpha ratio was negative in all participants. In maximum phonation time, 60% of the sample had decreased values. Visually, glottic closure deficiency was evident in 6 subjects, and 5 participants showed supraglottic activity contraction.Participants with Parkinson's disease exhibit alterations in voice acoustic parameters, maximum phonation time, and glottic configuration. These difficulties become more pronounced as the disease progresses and motor impairments become more evident.
Keywords: Parkinson`s disease; voice disorders; voice quality; Acoustic analysis